1996
DOI: 10.1136/thx.51.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Difference between functional residual capacity and elastic equilibrium volume in patients with chronic obstructive pulmonary disease.

Abstract: Background -A study was performed to determine the elastic equilibrium volume (Vr) of the respiratory system in patients with chronic obstructive pulmonary disease (COPD). Methods -Voluntary relaxed expiration from total lung capacity (TLC) was studied in three groups of subjects: seven patients with severe chronic airways obstruction (COPD), 10 normal subjects, and 15 subjects with restrictive disease. Results -In the normal subjects and the patients with restrictive disease voluntary relaxed expiration from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…The concept of time constant reflecting resistance times compliance of the respiratory system 25 is well accepted in passive expiration in normal subjects, although even there it has been shown that a single exponential does not describe the tidal expiratory pattern completely 26 . The time constants that we have measured during tidal expiration in normal subjects agree well with the theoretical 27 and measured 19,20 , 28 time constants of passive expiration quoted in the literature, and with the time constants of forced expiration measured in this study 18 . In the more complex situation of forced expiration, and tidal expiration in patients who are flow limited during quiet breathing, the interpretation of the flow/volume relationship is more problematic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The concept of time constant reflecting resistance times compliance of the respiratory system 25 is well accepted in passive expiration in normal subjects, although even there it has been shown that a single exponential does not describe the tidal expiratory pattern completely 26 . The time constants that we have measured during tidal expiration in normal subjects agree well with the theoretical 27 and measured 19,20 , 28 time constants of passive expiration quoted in the literature, and with the time constants of forced expiration measured in this study 18 . In the more complex situation of forced expiration, and tidal expiration in patients who are flow limited during quiet breathing, the interpretation of the flow/volume relationship is more problematic.…”
Section: Discussionsupporting
confidence: 88%
“…At end tidal lung volume, pressure is available to drive expiratory flow in a continued passive expiration. This is interrupted by the onset of inspiratory muscle activity, which opposes this expiratory pressure, and inspiration begins at a volume greater than the elastic equilibrium volume of the respiratory system 18 . The added EER operates by limiting flow early in expiration so that maximum flow is less and is reached later in expiration.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of dynamic hyperinflation at rest is more difficult to quantitate directly. By extrapolation of resting tidal expiratory flow curves and calculation of the area under the extrapolated curve, MORRIS and co-workers [14] estimated the average volume of dynamic hyperinflation in a group of patients with severe COPD to be 0.43 L. In a subsequent study [62], the same authors concluded that the relaxation volume may actually be less than RV. If an additional 0.6 L or so is added on exercise, the endexpiratory volume may increase to more than a litre above the relaxation volume.…”
Section: Breathlessness and Exercise Performancementioning
confidence: 96%
“…When the pneumothorax was resolved and the lung expanded the FRC and dead space increased providing little room for a normal tidal volume (Harada et al. 1984; Morris et al. 1996; Kozower et al.…”
Section: Discussionmentioning
confidence: 99%
“…The TLC can diminish with chronic pulmonary changes during pneumothorax. When the pneumothorax was resolved and the lung expanded the FRC and dead space increased providing little room for a normal tidal volume (Harada et al 1984;Morris et al 1996;Kozower et al 2003). The lung and pleural elastic architecture is formed during the fetal and neonatal periods but pulmonary disease may result in damage to pulmonary elastin and replacement with collagen thus increasing FRC and dead space (Shapiro et al 1991;Pierce et al 1995;Billet & Sharpe 2002).…”
Section: Discussionmentioning
confidence: 99%